Implementing SNOMED CT for Quality Reporting: Avoiding Pitfalls - Wade, G. (Applied Clinical Informatics, 2011)
Objective: To implement the SNOMED CT electronic specifications for reporting quality measures and to identify critical issues that affect implementation.Background: The Centers for Medicare and Medicaid (CMS) have issued the electronic specifications for reporting quality measures requiring vendors and hospital systems to use standardized data elements to provide financial incentives for eligible providers.Methods: The electronic specifications from CMS were downloaded and extracted. All SNOMED CT codes were examined individually as part of the creation of a mapping table for distribution by a vendor for incorporation into electronic health record systems. A qualitative and quantitative evaluation of the SNOMED CT codes was done as a follow up to the mapping project.Results: A total of 10643 SNOMED codes were examined for the 44 measures. The approved SNOMED CT code sets contain aberrancies in content such as incomplete IDs, the use of description IDs instead of concept IDs, inactive codes, morphology and observable codes for clinical findings and the inclusion of non-human content.Conclusion: Implementers of these approved specifications must do additional rigorous review and make edits in order to avoid incorporating errors into their EHR products and systems.
Keywords: SNOMED CT; electronic health records; national health policy